PRODUCTION OF MACROPHAGE AND INTERLEUKIN-8 MIGRATION INHIBITION FACTOR IN CHILDREN AND ADOLESCENTS SUFFERING FROM DESTRUCTIVE PULMONARY TUBERCULOSIS - M. M. Averbakh (Jr.); L. V. Panova; E. S. Ovsyankina (Туберкулез и болезни лёгких)
The goal of the study is to assess the changes in spontaneous and antigen-induced production of macrophages and interleukin-8 in destructive tuberculosis patients during the intensive phase of treatment. The cultures of whole blood of 38 destructive tuberculosis patients were used as a source of macrophages and interleukin-8 production, and the patients were divided depending on procalcitonin semiquantitative test (BRAHMS PCT-Q) results into the group of PCT+ (15 patients) and the group of PCT- (23 patients). Production of macrophages and interleukin-8 were assessed in the cultured blood for 20-22 hours. Antigen-induced synthesis of macrophages was assessed after adding 20 mkg/ml of PPD or 1 mkg/ml of ESAT 6/CFP 10. Production of cytokines was tested by enzyme immunoassay. It has been found that the rates of spontaneous production of macrophages or interleukin-8 in the cultured blood reflect the changes in the production of these factors and can be used without consideration of antigen-induced synthesis; spontaneous production of macrophages in patients with positive test for PCT confidently decreases and production of IL-8 confidently goes up by the 2nd month of anti-tuberculosis chemotherapy; changes in spontaneous production of macrophages di}er in patients with the various course of destructive tuberculosis (favorable, torpid, progressing). In the favorable course of the disease production of macrophages increases, in torpid or progressing ones – goes down or stays unchanged.